Effect of Different Organic Substrates on Reproductive Biology, Growth and Offtake of the African Night Crawler Earthworm (Eudrilus eugeniae) - Kabi, Fred; Kayima, Denis; Kigozi, Abasi; Mpingirika, Eric Zadok; Kayiwa, Ronald; Okello, Dorothy (Saly Portudal, Senegal, 2018)
Rapid growth and high fecundity of Eudrilus eugeniae makes it a commercial vermicomposting agent. The worm is also a rich protein source (50-70%CP) in livestock diets. The major question, however, is how do we promote earthworm production as a strategy for ecological livestock intensification and integration with crops through earthworm domestication as a source of protein and vermicompost. Reproduction characteristics, growth and offtake of E. eugeniae were studied using four organic substrates including abattoir waste (AW), cattle manure (CM), soya bean crop residue (SBCR) and a mixture of cattle manure and soya bean crop residue (CM+SBCR) aged 15 days. Irrespective of the substrate, length and biomass of earthworms increased at a decreasing rate between the 1st and 8th weeks. Clitellum appearance was initiated at 31.5±2.4, 32.8±3.2, 33.7±3.3 and 35.5±2.4 days for AW, CM,CM+SBCR and BCR, respectively, while cocoon initiation was at 69.0±1.4 (AW), 54.9±2.3 (CM), 51.7±1.7 (CM+SBCR) and 60.0±2.4 (SBCR) days. Organic substrate used affected reproductive biology,
Keywords: Clitellum; Cocoon initiation; Earthworm biomass; Hatchlings; Vermibeds